2008
DOI: 10.1093/brain/awn136
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal temporal difference reward-learning signals in major depression

Abstract: Anhedonia is a core symptom of major depressive disorder (MDD), long thought to be associated with reduced dopaminergic function. However, most antidepressants do not act directly on the dopamine system and all antidepressants have a delayed full therapeutic effect. Recently, it has been proposed that antidepressants fail to alter dopamine function in antidepressant unresponsive MDD. There is compelling evidence that dopamine neurons code a specific phasic (short duration) reward-learning signal, described by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
288
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(335 citation statements)
references
References 44 publications
35
288
7
Order By: Relevance
“…A number of neuroimaging experiments have been designed to evaluate the fundamental aspects of reward and punishment processing. Reduced neural activation elicited by rewards in regions of the medial frontal cortex and striatum has been observed (Knutson et al, 2008;Kumar et al, 2008;Pizzagalli et al, 2009). Consistent with a negative bias, enhanced punishment or loss-related activity has also often been observed, particularly in studies employing event-related potentials (e.g., Chiu & Deldin, 2007;Holmes & Pizzagalli, 2008), but equally so has been attenuated loss-related activity (Steele et al, 2007).…”
Section: Methods Subjectsmentioning
confidence: 93%
“…A number of neuroimaging experiments have been designed to evaluate the fundamental aspects of reward and punishment processing. Reduced neural activation elicited by rewards in regions of the medial frontal cortex and striatum has been observed (Knutson et al, 2008;Kumar et al, 2008;Pizzagalli et al, 2009). Consistent with a negative bias, enhanced punishment or loss-related activity has also often been observed, particularly in studies employing event-related potentials (e.g., Chiu & Deldin, 2007;Holmes & Pizzagalli, 2008), but equally so has been attenuated loss-related activity (Steele et al, 2007).…”
Section: Methods Subjectsmentioning
confidence: 93%
“…Some other studies investigated the dopamine model-related brain response in psychiatric disorders, such as depression (Kumar et al, 2008) or schizophrenia (Waltz et al, 2010), and tended to find reduced brain response in those disorders. Dopamine neuronal reward response can be captured in an algorithm that takes advantage of dopamine neurons responding to unexpected reward stimulus receipt or omission (Schultz, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…MDD is characterized by impaired cortico-limbic functioning, including dysfunction in (1) the cortical brain regions that mediate attention, reward-based decision making, and monitoring of emotional salience (Ressler and Mayberg, 2007;Seminowicz et al, 2004); (2) the subcortical brain regions that process affective stimuli (Kumar et al, 2008;Pizzagalli et al, 2009) and that modulate emotional memory formation and retrieval (Dillon et al, 2013); and (3) the coordinated interactions of distributed networks of limbiccortical pathways during processing of cognitive and affective information (Drevets et al, 2008;Northoff et al, 2011). Neuroimaging treatment outcome research has shown that MDD remission is associated with decreased activity in orbitofrontal and medial prefrontal cortex Kennedy et al, 2007), increased activity in hippocampus and dorsal cingulate cortex , and increased subcortical circuits involved in responses to rewards Stoy et al, 2012) and emotion regulation (Ressler and Mayberg, 2007).…”
Section: Introductionmentioning
confidence: 99%